1998
DOI: 10.1007/bf02783128
|View full text |Cite
|
Sign up to set email alerts
|

Multicountry estimation of dietary boron intake

Abstract: Dietary Reference Intakes are not yet established for boron (B), a naturally occurring trace element in the human diet. Estimated dietary B intakes provide useful information for planning and assessing diets in healthy populations. The countries selected for this study represent a wide variety of dietary patterns and have adequate nutrient databases (with the exception of B) and food consumption data. Large-scale nationwide survey data were provided by the US (1989-1991) and Germany (1985-1989). Survey data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 4 publications
1
21
0
1
Order By: Relevance
“…A study conducted in the USA revealed that the average daily exposure to B is around 1 mg in that country 29 . In another study reporting the results from four countries for adult males over 19 years of age, the daily B exposure values were reported as 1·04-1·11, 1·61-1·79, 1·89 -2·36 and 1·94-2·03 mg/d for the USA, Germany, Mexico and Kenya, respectively 30 . It might be suggested that the variations observed for the different countries probably reflect the differences in diet traditions.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the USA revealed that the average daily exposure to B is around 1 mg in that country 29 . In another study reporting the results from four countries for adult males over 19 years of age, the daily B exposure values were reported as 1·04-1·11, 1·61-1·79, 1·89 -2·36 and 1·94-2·03 mg/d for the USA, Germany, Mexico and Kenya, respectively 30 . It might be suggested that the variations observed for the different countries probably reflect the differences in diet traditions.…”
Section: Discussionmentioning
confidence: 99%
“…For vegetarian adults, these intakes are between 1.47 and 2.74 mg B/day for men and between 1.29 and 4.18 mg B/day for women. Among the top 50 B contributors, peanut butter, wine, raisins, peanuts, and other nuts are high in B [40,43].…”
Section: Average Fructoborate Intakementioning
confidence: 98%
“…Rainey et al stated that "very large variations in B intakes occur across the U.S. adult population," ranging as high as 9 mg/person/day [43]. Mean and 95th percentile B intakes were estimated as 1.17-2.42 mg/day for men and 0.96-1.94 mg/day for women.…”
Section: Average Fructoborate Intakementioning
confidence: 99%
“…It is found primarily in plant foods and the human daily boron intake in different countries is in the range of 0.89-2.12 mg/day (19). Boron essentiality in humans is still unclear.…”
Section: Boronmentioning
confidence: 99%